2016
DOI: 10.1016/j.ceramint.2015.08.179
|View full text |Cite
|
Sign up to set email alerts
|

Relating residual stresses to machining and finishing in silicon carbide

Abstract: Machining and surface finishing is essential in the processing of many ceramics, however, it can be detrimental to subsequent performance as it introduces residual stresses and structural defects. Using micro-Raman spectroscopy the residual stress and crystallinity of hotpressed SiC tiles was examined after finishing with several different methods. 514 nm and 633 nm lasers in both conventional and confocal settings enabled stress as a function of depth to be assessed. Single crystal, electronics grade SiC was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…To maintain the surface shape stability and ameliorate the mechanical properties of the workpiece material, hence, there is certainly need to effectively characterize and eliminate the additional residual stress with appropriate technique. At present, there are many reports on grinding residual stress and its elimination process and studies of the residual stress on the ground surface of SiC materials [34][35][36], but few reports on the characterization and elimination of residual stress for the ground surface of C/C-SiC composite material. In addition, the investigation on the machining of C/C-SiC composite material is mainly focused on unidirectional or 2D C/C-SiC composite.…”
Section: Smentioning
confidence: 99%
“…To maintain the surface shape stability and ameliorate the mechanical properties of the workpiece material, hence, there is certainly need to effectively characterize and eliminate the additional residual stress with appropriate technique. At present, there are many reports on grinding residual stress and its elimination process and studies of the residual stress on the ground surface of SiC materials [34][35][36], but few reports on the characterization and elimination of residual stress for the ground surface of C/C-SiC composite material. In addition, the investigation on the machining of C/C-SiC composite material is mainly focused on unidirectional or 2D C/C-SiC composite.…”
Section: Smentioning
confidence: 99%
“…Ample research has been performed on the residual stress in bonding structures [ 5 , 6 , 7 , 8 ]. Xiao et al found that residual stress could be reduced by starting the bonding while avoiding the corner of the path, turning the laser off gradually and heating the glass substrates [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…RS can also enhance the mobility of charge carriers in semiconductor devices [ 2 ]. Hence, RS play a central role regarding the performance of brittle structures, and their determination has been of considerable interest [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%